2005
DOI: 10.1093/jac/dki191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of subinhibitory concentrations of ciprofloxacin on Mycobacterium fortuitum mutation rates

Abstract: These data show that sub-MIC concentrations of fluoroquinolone significantly increase mutation rates and these data suggest that care must be taken to ensure that bacteria are not exposed to subinhibitory concentrations when adding quinolones to a regimen used to treat mycobacterial infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 36 publications
0
70
0
1
Order By: Relevance
“…It can be used when the number of mutational events per culture is high, i.e., Ն30. This method has been used to estimate rates of mutation of S. pneumoniae to fluoroquin-olone resistance and of Mycobacterium fortuitum to fluoroquinolone, macrolide, and aminoglycoside resistance (9).…”
Section: Calculation Methodsmentioning
confidence: 99%
“…It can be used when the number of mutational events per culture is high, i.e., Ն30. This method has been used to estimate rates of mutation of S. pneumoniae to fluoroquin-olone resistance and of Mycobacterium fortuitum to fluoroquinolone, macrolide, and aminoglycoside resistance (9).…”
Section: Calculation Methodsmentioning
confidence: 99%
“…Secondly, because of simple and plastic genomes of bacteria, the emergence of resistant mutants for a class of antibiotics due to one used from that class is more likely than imagined, at least for the chance factor. Moreover, it had been elucidated earlier that a drug resistant mutant in a population of 10 6 -10 8 cells is most likely, without any involvement of the widely-talked-about R-plasmids, conferring resistance [28] . It is also consensus that mechanisms of drug resistance are multidimensional and there may be the expression of certain genes, beta-lactamase that degrades the applied beta-lactam or cephalosporin antibiotics [29] , or carbapenemases, degrading meropenem or imipenem or altered channels in the cell membrane that would disallow antibiotics for the entry into cells of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of a sub-inhibitory concentration against environmental bacteria is still unknown. It was reported that FQs at concentrations 10-100 times weaker than the MIC induced the expression of a functional gene (16), mutations (11), and morphological changes (33) at the single cell level. The concentrations detected in this study were lower than those.…”
Section: Discussionmentioning
confidence: 99%